Pengaruh Sikap, Norma Subjektif, Efikasi Diri, Presepsi Kontrol Perilaku Terhadap Niat Berwirausaha Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Metro - Via, Mita; Siswoyo, Slamet Tedy (Jurnal Manajemen DIVERSIFIKASI, 2023)
This study aims to determine the effect of Attitude, Subjective Norm, Self-Efficacy, Perception of Behavioral Control on Entrepreneurial Intentions of Students of the Faculty of Economics and Business, University of Muhammadiyah Metro. The method used in this research is an explanatory survey with a quantitative approach. The explanatory survey method is used to predict and explain the relationship or influence of one variable to another. By using primary data which is done by collecting data through observation and questionnaires. With a total sample of 94 respondents taken from two undergraduate majors at the Faculty of Economics and Business from a total population of 1470. Sampling technique Non-probability Sampling with purposive sampling method, using the 10% solvin formula. The results of this study indicate that subjective norms and perceptions of behavioral control have a significant and significant effect on entrepreneurial intentions, while attitudes and self-efficacy have no and no significant effect on entrepreneurial intentions of students of the Faculty of Economics and Business, University of Muhammadiyah Metro.